Sonographic Findings of Axillary Masses: What Can Be Imaged in This Space?. (1st July 2013) - Park, Ji Eun; Sohn, Yu-Mee; Kim, Eun-Kyung
Abstract : The diagnosis of axillary masses can be challenging because various tumors can develop in parts of the axilla other than lymph nodes, even though we frequently encounter axillary masses in daily practice. These lesions include soft tissue masses associated with nontumorous conditions (accessory breast tissue and chronic granulomatous inflammation) and benign and malignant tumorous conditions (lipomas, epidermal inclusion cysts, lymphangiomas, fibroadenomas, schwannomas, malignant neuroendocrine tumors, and lymph node–associated diseases). In this pictorial essay, we display commonly encountered sonographic findings of various axillary lesions to assist in the differential diagnosis of axillary masses.